Early first trimester maternal 'high fish and olive oil and low meat' dietary pattern is associated with accelerated human embryonic development. Issue 12 (December 2018) - Parisi, Francesca; Rousian, Melek; Steegers-Theunissen, Régine; Koning, Anton; Willemsen, Sten; Vries, Jeanne; Cetin, Irene; Steegers, Eric
Abstract Background/objectives Maternal dietary patterns were associated with embryonic growth and congenital anomalies. We aim to evaluate associations between early first trimester maternal dietary patterns and embryonic morphological development among pregnancies with non-malformed outcome. Subjects/methods A total of 228 strictly dated, singleton pregnancies without congenital malformations were enrolled in a periconceptional hospital-based cohort. Principal component analysis was performed to extract early first trimester maternal dietary patterns from food frequency questionnaires. Serial transvaginal three-dimensional ultrasound (3D US) scans were performed between 6+0 and 10+2 gestational weeks and internal and external morphological criteria were used to define Carnegie stages in a virtual reality system. Associations between dietary patterns and Carnegie stages were investigated using linear mixed models. Results A total of 726 3D US scans were included (median: three scans per pregnancy). The 'high fish and olive oil and low meat' dietary pattern was associated with accelerated embryonic development in the study population (β = 0.12 (95%CI: 0.00; 0.24), p < 0.05). Weak adherence to this dietary pattern delayed embryonic development by 2.1 days (95%CI: 1.6; 2.6) compared to strong adherence. The 'high vegetables, fruit and grain' dietary pattern accelerated embryonic development in the strictly dated spontaneous pregnancy subgroup without adjustment for energy intake. Conclusions Early first trimester maternal dietary patterns impacts human embryonic morphological development among pregnancies without congenital malformations. The clinical meaning of delayed embryonic development needs further investigation.